“Cross-talk” between gut microbiome dysbiosis and osteoarthritis progression: a systematic review - Liu, Su; Li, Guoqing; Xu, Huihui; Wang, Qichang; Wei, Yihao; Yang, Qi; Xiong, Ao; Yu, Fei; Weng, Jian; Zeng, Hui (Frontiers in Immunology, 2023)
Objectives The aim of this systematic review was to summarize the available literature on gut microbiome (GMB) and osteoarthritis (OA), analyze the correlation between GMB and OA, and explore potential underlying mechanisms. Methods A systematic search of the PubMed, Embase, Cochrane, and Web of Science with the keywords “Gut Microbiome” and “Osteoarthritis” was conducted to identify the human and animal studies exploring the association between GMB and OA. The retrieval time range was from the database inception to July 31, 2022. Studies reported the other arthritic diseases without OA, reviews, and studies focused on the microbiome in other parts of the body with OA, such as oral or skin, were excluded. The included studies were mainly reviewed for GMB composition, OA severity, inflammatory factors, and intestinal permeability. Results There were 31 studies published met the inclusion criteria and were analyzed, including 10 human studies and 21 animal studies. Human and animal studies have reached a consistent conclusion that GMB dysbiosis could aggravate OA. In addition, several studies have found that alterations of GMB composition can increase intestinal permeability and serum levels of inflammatory factors, while regulating GMB can alleviate the changes. Owing to the susceptibility of GMB to internal and external environments, genetics, and geography, the included studies were not consistent in GMB composition analysis. Conclusion There is a lack of high-quality studies evaluating the effects of GMB on OA. Available evidence indicated that GMB dysbiosis aggravated OA through activating the immune response and subsequent induction of inflammation. Future studies should focus on more prospective, cohort studies combined with multi-omics to further clarify the correlation.